Learning Assessment in the Independent Curriculum - Candra Kristiyan; Sri Mujiatun (Universitas PGRI Semarang, 2023)
An expansion of the 2013 Curriculum, the tailored curriculum is designed to maximize learning outcomes according to student needs. Utilize the assessment findings to inform the design of the lessons at the start, middle, and conclusion of the learning process. An overview of assessments that are often utilized in stand-alone courses is what this research attempts to give. Utilizing a qualitative descriptive approach, research materials are recorded, processed, and library data is gathered. According to research, self-paced courses utilize three different kinds of evaluations: formative, summative, and initial or diagnostic learning assessments. Cognitive diagnostic assessment and non-cognitive diagnostic evaluation are the two categories of diagnostic evaluation.